Analisis Kewenangan Mahkamah Agung Dalam Judicial Review Terhadap Peraturan Perundang-Undangan di Bawah Undang-Undang - Dio Siaga Putra Pulungan; Ansorullah Ansorullah (Limbago: Journal of Constitutional Law, 2022)
This study aims to determine and analyze the authority of the Supreme Court in judicial review of the laws and regulations under the law and the legal consequences of the authority of the Supreme Court to instruct the makers of the regulations, in order to cancel the legal consequences caused by the laws and regulations. tested. The research method used is a normative juridical research type. The results of the study show that 1) The right of judicial review of laws and regulations at a lower level or under the law is the authority of the Supreme Court. The nature of the Supreme Court's Judicial Rights Decision, which is ex nunc or pro future, namely decisions that apply to the future. The Supreme Court in its decision stated that the statutory regulations requested for review were (1) invalid regulations or (2) not applicable to the public and (3) ordered the relevant agencies to revoke them; 2) the legal consequences of the RI Supreme Court decision Number 57/P/HUM/2019 against PKPU No. 3/2019 and PKPU No. 4/2019 that regarding the order to the KPU agency to revoke PKPU No. 3/2019 and PKPU No. 4/2019 which has been canceled within the 90-day deadline, is a logical consequence when a rule has been overturned by the Supreme Court. This provision is a form of affirmation of administrative actions that must be taken by the KPU that issued the regulation. The revocation must be carried out immediately, without the administrative action of the revocation, the Supreme Court's decision Number 57/P/HUM/2019 which has been declared to have no binding legal force is no longer enforceable.Keywords: Authority, Supreme Court, Judicial Review.